Residual ISI cancellation for OFDM with applications to HDTV broadcasting. - Dukhyun Kim
An iterative technique is developed for orthogonal frequency division multiplexing (OFDM) systems to mitigate the residual intersymbol interference (ISI) that exceeds the length of the guard interval. The technique, called residual ISI cancellation (RISIC), uses a combination of tail cancellation and cyclic restoration and is shown to offer large performance improvements. The effects of imperfect channel estimation are also considered. The RISIC algorithm is applied to a typical terrestrial high-definition television (HDTV) broadcasting system that uses a concatenated coding scheme for error control. Results show that the RISIC algorithm can effectively mitigate residual ISI on static or slowly fading ISI channels
Keywords: HDTV broadcasting; OFDM systems; RISIC algorithm; Concatenated coding; Cyclic restoration; Error control; Guard interval length; Imperfect channel estimation; Intersymbol interference; Iterative technique; Orthogonal frequency division multiplexing; Residual ISI cancellation; Slowly fading ISI channels; Static fading ISI channels; Tail cancellation; Terrestrial high-definition television; Trellis codes